The flexibility for a sustainable Social Housing: the case of Preturo (AQ) - Radogna, Donatella (TECHNE - Journal of Technology for Architecture and Environment, 2012)
The presented research work proposes a study about the ≪flexibility≫ requirement, aiming to define its role in social housing requalification. For the Preturo A.T.E.R. settlement, characterized by considerable lack of technological units and performance gaps, we propose systems adaptable as for the variability of the dwelling, working and socialization needs for settled or to be settled users. The originality of the work consists in the identification of the flexibility as sustainable functional requalification strategy, also aware that the post-industrial buildings predisposition to transformation, given by their deterioration conditions, and the performance fitting possibilities are directly proportional.